PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS MODEL PROBLEM BASED LEARNING TEMA PAHLAWANKU KELAS IV SD SWASTA PAB 33 SIDODADI - Dea Anastya Safira; Beta Rapita Silalahi (Bajang Institute, 2025)
This study aims to determine the design of the development of teaching materials based on Problem-Based Learning in learning Theme 4 My Hero, grade IV of SD Swasta PAB 33 Sidodadi and to determine the feasibility of teaching material products based on the Problem-Based Learning model in learning Theme 4 My Hero, grade IV of SD Swasta PAB 33 Sidodadi. In this study, the researcher used a research and development design which is better known as Research and Development (R&D). The subjects of the trial in the development of thematic teaching materials based on the Problem Based Learning model on the theme of my hero are validators, material experts and textbook experts. The object of this study is a thematic textbook based on the Problem Based Learning model. The product developed is a teaching material based on Problem Based Learning on the theme